Heritage Branding Strategy Formulation For Tjong A Fie Mansion - Putra Prawira, Anggiea; Rizky Mutiaz, Intan (The Indonesian Journal of Business Administration, 2016)
Abstract. The purpose of the establishment of Tjong A Fie Mansion is to revitalize one of the national heritages building and also as a comprehensive representation of Chinese-Indonesian culture in Indonesia. To achieve its competitive advantage, Tjong A Fie Mansion needs to distinguish itself in travel industry and offers various products and services which is different and better than its competitors in the market. Tjong A Fie Mansion needs to focus on its heritage branding optimization since branding plays an important role for heritage site. It represents the core essence and enduring characteristics of a destination. The branding of heritage sites as a tourist destination will able to attract a lot of numbers of new tourists through support the enhancement of the site’s attractiveness through the utilization of historical and cultural heritage. The perceived image of the visitors to the mansion needs to be realistic and for it to be a positive experience to avoid the three place branding gaps; strategy, performance and satisfaction, to occur. Hence, the visitors’ experiences must equivalent with the expectations generated by the marketing. Tjong A Fie Mansion needs to implement business-derived strategic planning in ways that will benefit the mansion and the stakeholders. The newly established STP strategy will assist the management to create the perfect strategy in marketing and the delivery of the mansion’s brand image to be ahead in the industry. Keyword:  Heritage, Branding, Tourism, Marketing Mix, Culture